Challenges in dosimetry of particle beams with ultra-high pulse dose rates. (October 2020) - Romano, F.; Subiel, A.; McManus, M.; Lee, N. D.; Palmans, H.; Thomas, R.; McCallum, S.; Milluzzo, G.; Borghesi, M.; McIlvenny, A.; Ahmed, H.; Farabolini, W.; et al.
Abstract: Recent results from pre-clinical studies investigating the so-called FLASH effect suggest that the ultrahigh pulse dose rates (UHPDR) of this modality reduces normal tissue damage whilst preserving tumour response, when compared with conventional radiotherapy (RT). FLASH-RT is characterized by average dose rates of dozens of Gy/s instead of only a few Gy/min. For some studies, dose rates exceeding hundreds of Gy/s have been used for investigating the tissue response. Moreover, depending on the source of radiation, pulsed beams can be used with low repetition rate and large doses per pulse. Accurate dosimetry of high dose-rate particle beams is challenging and requires the development of novel dosimetric approaches, complementary to the ones used for conventional radiotherapy. The European Joint Research Project "UHDpulse" will develop a measurement framework, encompassing reference standards traceable to SI units and validated reference methods for dose measurements with UHPDR beams. In this paper, the UHDpulse project will be presented, discussing the dosimetric challenges and showing some first results obtained in experimental campaigns with pulsed electron beams and laser-driven proton beams.